Characterizing benzene series (BTEX) pollutants build-up process on urban roads: Implication for the importance of temperature. (November 2018) - Liu, An; Hong, Nian; Zhu, Panfeng; Guan, Yuntao
Abstract: Benzene series (BTEX) pollutants which are generated by traffic can deposit (build-up) on urban road surfaces. When they are washed-off by stormwater runoff, BTEX are toxic to ecological and human health if the stormwater is reused. To understand the risk posed by BTEX, it is essential to have an in-depth investigation on BTEX build-up, one of the most important stormwater pollutant processes. This study analysed the relationship between BTEX build-up and BTEX build-up's influential factors. The outcomes confirmed an important role of climatic factors (particularly temperature) on influencing BTEX build-up. This has not been considered in previous stormwater studies although this has been widely focused in atmospheric pollution. BTEX build-up loads were generally higher and the variability was low in dry seasons with low temperature such as winter and spring. Additionally, the influence of temperature on BTEX build-up on urban road surfaces is more important in the case of larger particles (such as >75 μm) than smaller particles. The study also showed that petrol station areas have a potential to export stormwater runoff with high BTEX concentrations, compared to typical urban roads. This is particularly applicable in winter and spring. These outcomes can provide useful guidance to improving stormwater quality modelling approaches, especially relevant to estimation of BTEX concentrations in the stormwater. Graphical abstract: Image 1 Highlights: BTEX build-up loads were high and the variability was low in low temperature. Petrol station areas have a potential to export highly BTEX polluted stormwater. Outcomes provide guidance to improving stormwater quality modelling approaches. Abstract : The importance of temperature in BTEX build-up and hence resulting urban road stormwater quality is confirmed.